Addictive behavior and incident gallstone disease: A dose–response meta-analysis and Mendelian randomization study - Bai, Ye; Zhang, Min; Cui, Huijie; Shan, Xuefeng; Gu, Dongqing; Wang, Yutong; Tang, Mingshuang; Wang, Xin; Jiang, Xia; Zhang, Ben (Frontiers in Nutrition, 2022)
Background Previous studies have suggested associations between addictive behavior and gallstone disease (GSD) risk, yet conflicting results exist. It also remains unclear whether this association is causal or due to confounding or reverse associations. The present study aims to systematically analyze the epidemiological evidence for these associations, as well as estimate the potential causal relationships using Mendelian randomization (MR). Methods We analyzed four common addictive behaviors, including cigarette smoking, alcohol intake, coffee, and tea consumption (N = 126,906–4,584,729 participants) in this meta-analysis based on longitudinal studies. The two-sample MR was conducted using summary data from genome-wide associations with European ancestry (up to 1.2 million individuals). Results An observational association of GSD risk was identified for smoking [RR: 1.17 (95% CI: 1.06–1.29)], drinking alcohol [0.84 (0.78–0.91)], consuming coffee [0.86 (0.79–0.93)], and tea [1.08 (1.04–1.12)]. Also, there was a linear relationship between smoking (pack-years), alcohol drinking (days per week), coffee consumption (cups per day), and GSD risk. Our MRs supported a causality of GSD incidence with lifetime smoking [1.008 (1.003–1.013), P = 0.001], current smoking [1.007 (1.002–1.011), P = 0.004], problematic alcohol use (PAU) [1.014 (1.001–1.026), P = 0.029], decaffeinated coffee intake (1.127 [1.043–1.217], P = 0.002), as well as caffeine-metabolism [0.997 (0.995–0.999), P = 0.013], and tea consumption [0.990 (0.982–0.997), P = 0.008], respectively. Conclusion Our study suggests cigarette smoking, alcohol abuse, and decaffeinated coffee are causal risk factors for GSD, whereas tea consumption can decrease the risk of gallstones due to the effect of caffeine metabolism or polyphenol intake.